Green synthesis, characterizations of silver nanoparticles using sumac (Rhus coriaria L.) plant extract and their antimicrobial and DNA damage protective effects - Gur, Tuğba (Frontiers in Chemistry, 2022)
Recently, nanoparticles produced by green synthesis have started to be used in a wide area around the world due to many advantages such as being environmentally friendly, economical and non-toxic. Sumac (Rhus coriaria L.) is a spice widely utilized in the Mediterranean area and is evaluated a healthful food ingredient. The useful worth of sumac is well known in public medicine. The obtained reports revealed that sumac has phytochemical, nutritional and medical properties as a utility nutriment. Sumac is a plant that is plentiful in diverse polyphenolic contents such as flavonoids, tannins and phenolic acids and is frequently used among the people. In this study, the characterizations of silver nanoparticles, which we produced by green synthesis by using sumac (Rhus coriaria L.) plant, were made by TEM, AFM, XRD, UV-Vis, and FTIR analyzes, and the results revealed various properties of Rc-AgNPs. As the concentrations of Rc-AgNPs increased, the protection against plasmid DNA damage increased and provided a strong protection at the highest concentration of 1000 µg/mL. However, it exhibited very good antibacterial effects with the disc diffusion test against various bacterial strains and fungi. According to the results obtained in line with the antibacterial tests, the inhibition zone diameters of the silver nanoparticles against Bacillus cereus, Bacillus subtilis, Enterococcus faecalis, Pseudomonas aeruginos bacteria and Candida albicans fungus, respectively. It was found to be 11 mm, 14 mm, 10 mm, 10 mm and 12 mm. As a result, sumac-mediated AgNP synthesis can be considered as a new approach model to develop anti-DNA damage and antimicrobial drugs that are inexpensive and environmentally friendly.